Study Of The Effect Of Variations In Fiber Orientation On The Tensile Strength Properties Of Polyester Composites Reinforced Abaca Fiber - Abubakar Dabet; Nurul Islami; Aljufri; Ferry Safriwardi; Azhar Syahputra; Muhammad Yusri (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
A composite is a material formed from a combination of two or more constituent materials using a heterogeneous mixing process, whose mechanical properties vary. The aim of this research is to compare the tensile strength values ​​of abaca banana stem fiber polyester composites with variations in fiber orientation. The fiber orientation used is parallel, random and woven. The method used is a hand lay-up press with a fiber volume fraction of 30% and the resin itself uses BQTN 157 EX polyester resin with a hand lay-up method using a glass mold. The test was carried out by tensile testing using the ASTM D3039 measurement standard and macro photos. The results of research on tensile testing show that composites with variations in parallel fiber orientations reinforced with abaca banana stem fibers have an average tensile strength of 39.63 MPa, variations in random fiber orientation have an average tensile strength of 32.87 MPa and variations in fiber orientation woven has an average tensile strength of 25.90 MPa. From the results of macro photo fracture observations, it was found that the type of fracture is a brittle fracture on an uneven fracture surface which causes fiber pull-out where the fibers appear to be coming out of the specimen because the matrix and fibers are not strongly bonded and the fracture is also caused by voids near the fibers.